Novel functional TPE polymers: aggregation-induced emission, pH response, and solvatochromic behavior - Huang, Wei; Bender, Markus; Seehafer, Kai; Wacker, Irene; Schröder, Rasmus R.; Bunz, Uwe H. F. (Macromolecular rapid communications, 2019)
Four tetraphenylethylene (TPE)-based aryleneethynylene polymers with amino or nitro groups are reported. They display strong aggregation-induced emission (AIE). The functional groups trigger acidochromic changes in the emission behavior of these polymers. Amino-substituted P1-P3 exhibit pH response through protonation of the amino groups. The position of the amino groups (on TPE or the side chains) influences the fluorescence intensity or emission wavelength as a response to different pH values. Nitro-P4 is solvatochromic due to its donor-acceptor structure. AIE, intramolecular charge transfer, and Förster resonance energy transfer define the fluorescence-based performance of the polymers. The amino-functionalized TPE polymers show excellent nitroarene-sensing performance. P4 is less effective than the amino polymers. A sensor array based on P1-P3 identifies 12 different nitroarenes in water.